Selection of dancer member using simple additive weighting - Adela, Hana; Azmi Jasmi, Kamarul; Basiron, Bushrah; Huda, Miftachul; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
Travel and dance form in Indonesia is closely related to the development of community life, both in terms of ethnic structure and within the scope of the unitary state.Â This study determines the criteria forÂ selecting dancer members andÂ how to apply theÂ qualifiedÂ Simple method.Â Based on predetermined criteria is the ability to dance physical flexibility, skilled, nimble, confident, have the ability, fill out the form, and certificate of achievement.Â From the results obtained values then V1, V2, V3, V4, V5Â is aÂ member ofÂ a qualifiedÂ dancerÂ and has a highest value with a score of 100 which was obtained from V2.Â